PENGARUH LAMA PENYIMPANAN DAN KONSENTRASI NATRIUM BENZOAT TERHADAP KADAR VITAMIN C CABAI MERAH (Capsicum annuum L) (The Effect Of Length Storage And Sodium Benzoat Concentration On The Vitamin C Levels Of Red Chili (Capsicum annuum L) - Oktoviana, Yanti; Aminah, Sitti; Sakung, Jamaluddin (Universitas Tadulako, 2012)
Red chillies (Capsicum annuum L) are considerable horticultural crops widely grown in Indonesia, which has a high value and demand in market. Besides it contains higher vitamin C (ascorbic acid) and beta-carotene than other fruits such as papaya, mango, pineapple and watermelon, red chillies has a very low storability as it is susceptible to decay and the over-production of chili resulting in postharvest decay. To prevent the decay, red chillies are preserved using preservatives. Preservative used in this study is sodium benzoate since it is claimed as an effective against fungi. This study aimed to determine the effect of the concentration of sodium benzoate against storage time of red chillies (Capsicum annuum L) and also to determine the effect of the concentration of sodium benzoate levels towards vitamin C in preserved red chili. The method used in this experiment was a laboratory experiment using a visible spectrophotometry. The results showed that the use of sodium benzoate as a preservative can extend the storability of red chillies and sodium benzoate concentration also affect levels of vitamin C contained in red chillies. The level obtains at the highest concentration of 1.5% which is 54 mg/100 g with 8 days of storability.